Analysıs Of Research On Navoı’s Phılosophıcal Belıefs - Elmurad Nasrullaev, Farida Israilova, Obida Fayzullaeva (International Journal of Advanced Science and Technology, 2020)
This article discusses the secrets of Hazrat Navoi’s artistic mastery, his philosophical beliefs, the artistic means he used, his rhymes and syllables, and his mastery of weights.